Design and evaluation of a mobile application interface for stokvel groups: an Eastern Cape case study - Tembo, Masharty (Department of Computer Science, 2025)
This dissertation investigates the potential use of mobile applications to facilitate the management of Stokvels - informal savings groups - in rural South African communities. Amid challenges like mismanagement, lack of transparency, and constraints posed by the COVID-19 pandemic, digital solutions may offer effective remedies. The research seeks to comprehend the functioning of Stokvels, explore the activities that foster social capital, and design a user-friendly mobile application prototype through usability testing and qualitative thematic analysis of focus group data. The study adopts a user-centred approach involving initial requirement gathering, artefact creation for usability testing, and high-fidelity prototype evaluation. Data was collected through a focus group from the Imijelo Yophuhliso Foundation, and a WhatsApp chatbot prototype was tested and refined iteratively. Key findings revealed that users needed a comprehensive platform for record-keeping, improved communication channels, and an efficient loan request system. Despite the existing digital divide, a readiness to adopt technology was evident. Usability testing of the prototype yielded a 100% task completion rate, pointing to a solid foundational design, but also identified areas for improvement. Activities fostering social capital, like shared group identity, progress monitoring, effective communication, shared financial responsibility, and mutual aid, were identified as critical for integration into the mobile application. The study contributes significantly to the literature on digital financial inclusion, usability testing, and the role of mobile technologies in poverty alleviation. However, limitations such as language barriers, a short research timeframe, and a focus on a specific type of Stokvel warrant attention for future research. This study holds implications for similar communities in South Africa and other parts of Africa and researchers interested in digital adoption in informal institutions in low-income areas.